Critical micelle concentration of sodium dodecyl sulphate in pure water and in methanol-water mixed solvent media in presence and absence of KCl by surface tension and viscosity methods - Niraula, Tulasi Prasad; Bhattarai, Ajaya; Chatterjee, Sujeet Kumar (BIBECHANA, 2014)
Careful measurements of surface tension and viscosity of sodium dodecyl sulphate (SDS) in presence and absence of KCl in pure water and methanol-water mixed solvent media containing 0.1, 0.2, 0.3 and 0.4 volume fractions of methanol at 308.15 K are reported. The concentration of KCl is 0.01M. The concentration of SDS varies from 4.86×10-3 to 29.56×10-3 mol.l-1. The critical micelle concentration (cmc) increases with increase in percentage of methanol and decreases with addition of salt. DOI: http://dx.doi.org/10.3126/bibechana.v11i0.10388 BIBECHANA 11(1) (2014) 103-112